Photonic Crystals: Template‐Directed Directionally Solidified 3D Mesostructured AgCl–KCl Eutectic Photonic Crystals (Adv. Mater. 31/2015). (13th August 2015) - Kim, Jinwoo; Aagesen, Larry K.; Choi, Jun Hee; Choi, Jaewon; Kim, Ha Seong; Liu, Jinyun; Cho, Chae‐Ryong; Kang, Jin Gu; Ramazani, Ali; Thornton, Katsuyo; Braun, Paul V.
<x xml:space="preserve">Abstract</x> New optically active three‐dimensionally (3D) mesostructured AgCl–KCl eutectic photonic crystals and a 3D mesoporous AgCl inverse opal structure emerge from the combination of the characteristic periodic structure of a 3D template, and the native self‐organizing structure of a AgCl–KCl eutectic. This is described by K. Thornton, P. V. Braun, and co‐workers on page 4551.